(untitled) (Fiep Bulletin - online, 2012)
Traditional communities remnants of ancient historiography and quilombos reappear in the agenda of the current political discussion with another guise, the moment is the political interest of "social inclusion" and the historical process, political, social and economic interests is specific to the inclusion of remedial policies for black populations. The indices and surveys show that the socio-economic profile of African descent in Brazil is not good, especially the remnants of ancient communities quilombos, where much of it is in a state of total abandonment of public authorities, like the communities of the interior of Alagoas, in specific. The objective, therefore, conduct a case study in community Jacu mocó, correlating anthropometry as a tool for nutritional surveillance of children, taking into account the specific historical and socioeconomic conditions. The survey characterized as quantitative, descriptive and transversal (Thomas & Nelson, 2007). It was found that there is a nutritional deficiency and stunting in 70% of the children assisted in the sample. The body mass index in male children obtained a score of 15.65 and female children had an average of 15.40. In relation to the percentage of fat, male children had an average of 12.15% and female children had an average of 16.03%. For the waist / hip ratio, male children had an average of 93.6% and female children data about height average of 89.5%. Dwarfism is still object of research that needs to be further explored. It is noteworthy, therefore, the need to extend and cover a number of studies which will contribute to the integration and construction of public policies for sustainable development, according to ethnicity, social organization and the community’s cultural remnant of Quilombo.